DECLINED COMMERCIAL CATCH OF GANGETIC INDIAN MAJOR CARPS AT ALLAHABAD - JHA, D N; JOSHI, K D; TYAGI, R K (Journal of the Inland Fisheries Society of India, 2021)
Fish and fisheries of rivers are an important source of livelihood for the people inhabiting on its bank. Since multifarious stressors are operating on the river Ganga, tremendous alterations have been registered in its discharge, velocity, substratum, quality of the abiotic and biotic parameters. Due to these aberrations, the fish catch from the river Ganga has been declined and fishery of river has changed. Commercial fish catch of Indian major carp (IMC) from Ganga river system at Allahabad showed variations since 1955 to 2015. Since Ganga river system is known as original abode of IMC, hence there is need to propagate and conserve these species in the river system. The sizeable population of IMC in the river would also help the thousands of fishers residing along the river bank in augmentation of their livelihood security, as these species fetch lucrative price and highly demanded in the market by the fish eaters. Key word: Ganga, Fish landing, Indian major carps, Allahabad